Differential adherence capacities of pneumococcal clinical isolates at different growth states to human lung epithelial cells (in vitro) - Desa, M.N.; Sekaran, S.D.; Vadivelu, J.; Parasakhti, N. (2007)
Pneumococcal adherence to surface mucosa of human lung nasopharynx is the first step before progression to colonization and invasion leading to pneumococcal diseases. This study was undertaken to evaluate the adherence capacities of two clinically important serotypes (23-valent Pneumovax vaccine types) of pneumococci at different states of growth to human lung epithelial cells (in vitro).